A review on the application of natural rubber as asphalt modifier - Ansari, Anwaar Hazoor; Mohd Jakarni, Fauzan; Muniandy, Ratnasamy; Hassim, Salihudin (IOP Publishing, 2021)
Natural rubber as bio-modifier of bitumen and asphalt mixtures has shown to have some beneficial effects. As initially produced, natural rubber consists of polymers of the organic compound isoprene, with minor impurities of other organic compounds, plus water. Natural rubber can consist of various forms including as latex, which is a sticky, milky colloid; cup lump which is a coagulated latex and ribbed smoke sheet. Natural rubber is used extensively in many products and applications, either alone or in combination with other materials as it has a large stretch ratio and high resilience, and extremely waterproof. Due to these properties together with a chemical composition which can be classified as elastomers, natural rubber modification can improve the performance of conventional asphalt mixtures that are currently faced limitation against increased traffic loading and higher axle loads together with the effect of ageing, moisture, and temperature. Also, the application of natural rubber as part of the construction of asphalt mixture pavement might support the national agenda to boost rubber industry. This paper will review the application of various forms of natural rubber as modifier either in bitumen or asphalt mixtures based on previous studies done by other researchers. Numerous studies have been conducted based on different types and composition of natural rubber to determine the performance especially in terms of rutting and fatigue cracking properties.